2007
DOI: 10.1051/gse:2007040
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and metabolic aspects of androstenone and skatole deposition in pig adipose tissue: A review(Open Access publication)

Abstract: -High levels of androstenone and skatole in fat tissues are considered the primary causes of boar taint, an unpleasant odour and flavour of the meat from non-castrated male pigs. The aim of this article is to review our current knowledge of the biology and genetic control of the accumulation of androstenone and skatole in fat tissue. Two QTL mapping studies have shown the complexity of the genetic control of these traits. During the last ten years, several authors have taken a more physiological approach to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
(82 reference statements)
1
26
0
Order By: Relevance
“…The remaining boar taint QTL previously identified on SSC6 for smell intensity [39], subjective pork odour and skatole measurements [17,40] are located distal or proximal on SSC6. None of the other QTL studies investigating androstenone or sensory panel traits identified effects on SSC6 [19,24,39]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining boar taint QTL previously identified on SSC6 for smell intensity [39], subjective pork odour and skatole measurements [17,40] are located distal or proximal on SSC6. None of the other QTL studies investigating androstenone or sensory panel traits identified effects on SSC6 [19,24,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Two linkage studies using microsatellite markers have identified several QTL regions for androstenone and skatole in experimental crosses with 485 and 187 F2 animals, respectively [17,18] pointing towards several areas in the genome affecting these traits. Also, single candidate genes involved in androstenone synthesis and metabolism of androstenone and skatole have been analyzed at the level of RNA and protein expression and in single SNP association studies (reviewed by Robic et al, 2008 [19]). However, no conclusive results showing functional mutations affecting androstenone and skatole levels in fat tissue have been described until now.…”
Section: Introductionmentioning
confidence: 99%
“…Androstenone, a more urine smelling compound is also accumulated in adipose tissue. It is biosynthesised from cholesterol in boar testes (reviewed in [2]). It was previously found that levels of both compounds are linked to sexual maturity of male pigs [3] and that there is a relationship between their metabolisms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes and regulatory proteins relating to both androstenone and skatole concentrations have been reviewed in several papers [2] and [15]. Androstenone along with other steroid hormones are synthesized from pregnenolone or progesterone through the formation of 5,16-androstadien-3β-ol or 4,16-androstadien-3-one, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation